ANALISIS USAHA AGROINDUSTRI JAMU TRADISIONAL SKALA RUMAH TANGGA DI KELURAHAN LABUH BARU TIMUR KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Edwina, Susy; ', Sarman; Rifa’i, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze the revenues, the value added, efficiency, and break even point of traditional herbal medicine agroindustry. The results of this study indicate that the traditional herbal medicine agroindustries in the procurement of primary ingredient and supplementary ingredients did not have a problem. Traditional herbal medicine agroindustries used the traditional technologies and processing was manually. The average gross revenues as much as Rp3,925,480.00 /month or as much as Rp111,614.44/kg of primary ingredient. The average net income Rp1,005,239.79/month or as much as Rp28,582.31/kg of primary ingredient.The average of the families employment income Rp2,882,017.57/ month or as much as Rp81.945,34 /kg of primary ingredient.  The average of value added of the traditional herbal medicine agroindustries Rp2,904,689.87/month or as much as Rp82,589.99/kg of primary ingredient. While the traditional herbal medicine agroindustries was efficient at the RCR average of 1.34, meaning that the traditional herbal medicien agroindustries effort is feasible and efficient to be developed. Keywords: business analysis, traditional herbal medicine agroindustries